Quantum Communication and Quantum Networking First International Conference, QuantumComm 2009, Naples, Italy, October 26-30, 2009, Revised Selected Papers - Sergienko, Alexander; Pascazio, Saverio; Villoresi, Paolo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the First International Conference on Quantum Communication and Quantum Networking, QuantumCom 2009, held in Naples, Italy, in October 2009. The 38 full papers were selected from numerous submissions. This conference has been devoted to the discussion of new challenges in quantum communication and quantum networking that extends from the nanoscale devices to global satellite communication networks. It placed particular emphasis on basic quantum science effects and on emerging technological solutions leading to practical applications in the communication industry, culminating with a special section on Hybrid Information Processing. .
QuantumComm 2009 -- Tailoring the Spatio-temporal Bandwidth of Biphotons via the Non-factorable Structure of Entanglement -- Entanglement Generation by a Three-Dimensional Qubit Scattering: Concurrence vs. Path (In)Distinguishability -- Multipartite Entangled Codewords for Gaussian Channels with Additive Noise and Memory -- High-Speed Single-Photon Detection Using 2-GHz Sinusoidally Gated InGaAs/InP Avalanche Photodiode -- Local Transformation of Two EPR Photon Pairs into a Three-Photon W State Using a Polarization Dependent Beamsplitter -- Entanglement Degree Characterization of Spontaneous Parametric-Down Conversion Biphotons in Frequency Domain -- Matter-Matter Entanglement for Quantum Communication -- Manipulating Frequency Entangled Photons -- Ground-State Entanglement Gives Birth to Quantum Energy Teleportation -- Network Games with Quantum Strategies -- Optical Free-Space Communication on Earth and in Space Regarding Quantum Cryptography Aspects -- Feasibility Analysis for Quantum Key Distribution between a LEO Satellite and Earth -- Enhanced Free Space Beam Capture by Improved Optical Tapers -- Entanglement Based Quantum Key Distribution Using a Bright Sagnac Entangled Photon Source -- Solutions for Redundancy-Free Error Correction in Quantum Channel -- Two-Way Quantum Communication in a Single Optical Fiber with Active Polarization Compensation -- Passive Decoy State Quantum Key Distribution -- QKD in Standard Optical Telecommunications Networks -- Properties of Cascade Switch Superconducting Nanowire Single Photon Detectors -- Nano-Optical Studies of Superconducting Nanowire Single Photon Detectors -- Examples of Quantum Dynamics in Optomechanical Systems -- A 2D Electron Gas for Studies on Tunneling Dynamics and Charge Storage in Self-assembled Quantum Dots -- Special Session on Hybrid Information Processing (HIP) -- Entanglement Purification with Hybrid Systems -- Few Atom Detection and Manipulation Using Optical Nanofibres -- An Error Model for the Cirac-Zoller cnot Gate -- Poster Session -- Fiber Coupled Single Photon Detector with Niobium Superconducting Nanowire -- Superconducting Nanowire Single-Photon Detectors for Quantum Communication Applications -- Interferometric Technique for Density Matrix Reconstruction by On/Off Detectors -- Simulating BB84 Protocol in Dephasing Qubit Channel -- Using Multi-particle Entanglement in Secure Communication Scenarios -- Subband Tunneling and Coulomb Effects in Coupled Quantum Wells -- Generation of Non-Gaussian Quantum State in Telecommunication Band -- Workshop on Quantum and Classical Information Security -- Efficiency of the Eavesdropping in B92 QKD Protocol with a QCM -- Improvement of Lattice-Based Cryptography Using CRT -- The Case for Quantum Key Distribution -- On QKD Industrialization -- CTES Factorization Algorithm.
Keywords: Computer science; Computer communication systems; Special purpose computers; Data encryption (Computer science).; Artificial intelligence; Quantum physics; Quantum optics; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Quantum Physics; Quantum Optics; Special Purpose and Application-Based Systems; Data Encryption; Electronic books